Stacking Structure of Vaterite Revealed by Atomic Imaging and Diffraction Analysis - Okumura, Taiga; Takahashi, Gen; Suzuki, Michio; Kogure, Toshihiro (Chemistry : a European journal, 2024)
Anhydrous calcium carbonate crystals exist as three polymorphs: calcite, aragonite, and vaterite. Although vaterite is a metastable phase rarely found in the geological environment, it is intriguing that various biominerals are composed of vaterite. The processes of stable vaterite formation in biological systems cannot be understood without elucidating the nature of vaterite. The crystal structure of vaterite has been discussed for nearly a century but is still an open question. Here we propose the actual structure of vaterite by combining atomic imaging and diffraction analysis with simulations of disordered stacking sequences. Vaterite basically appears as layers of hexagonal calcium planes and carbonate (CO32−)‐containing sheets stacked with +60°, −60°, or 180° rotations from the underlying layer. However, equivalent carbonate positions in alternating layers are forbidden, and four‐layer stacking in which the fourth layer rotates 180° relative to the first layer are predominant, forming an orthogonal reciprocal lattice in diffraction patterns. These stacking characteristics replicate the intensity distribution in the electron and X‐ray diffraction patterns. This study has almost completely elucidated the crystal structure and stacking sequence of vaterite. Our findings provide insights into the thermodynamic stability of vaterite, which facilitates comprehension of the biomineralization processes and growth dynamics of calcium carbonate. After a century of discussion, the atomic arrangements of vaterite are fully visualized and described as a layer structure consisting of calcium planes and carbonate (CO32−)‐containing sheets. The layers are stacked with +60°, −60°, or 180° rotations from the underlying layer under two constraints: (i) carbonate ions cannot occupy equivalent positions in alternate layers, and (ii) the stacking sequences with orthogonal components are dominated.